Influential Factors of Fertile Age Couples (PUS) in the Selection of Long-Term Contraception Methods (MKJP) in the Work Area of the Medan Community Health Center - Nelly Mariati; Sarma Lumban Raja; Rina Hanum (Newinera Publisher, 2021)
Efforts to reduce population growth are carried out by controlling births through family planning. The contraceptive method recommended by the government is the Long Term Contraception Method (MKJP) because it is more efficient, safe, and effective. Data at the state, provincial, district / city level, as well as data from the Community Health Center, the use of non-MKJP (73.4%) is more desirable than the Long-Term Contraception Method (MKJP) (26.6%). Many factors cause someone to choose to use MKJP based on Green's theory. The purpose of this study was to analyze the factors that influence EFA in the selection of the Long-Term Contraception Method (MKJP). This type of research is an analytic survey with a cross sectional design. The research was conducted in the working area of ​​the Medan Teladan Community Health Center. The population of PUS mothers was 2,897 people, and the sample was obtained 110 people. Data analysis was univariate, bivariate using chi-square and multivariate using multiple logistic regression at the 95% confidence level ( = 0.05). The results showed that the variables that had an effect on the selection of MKJP in the Medan Teladan Community Health Center were knowledge (p = 0.002), family / husband support (p = 0.038), and the role of cadres (p = 0.001). The variables that had no effect were attitude (p = 0.153), accessibility (p = 0.061), and peer support (p = 0.098). The most dominant factor was the role of the cadre variable with a value of Exp (B) / OR = 8.819, which means that respondents who stated that the role of cadres was supportive had the opportunity to choose MKJP by 8.8 times higher than stating that the role of cadres was not supportive. The conclusion of this study is that the selection of MKJP by Fertile Age Couples (PUS) is influenced by knowledge, family / husband support, and the role of cadres. It is recommended that KB cadres increase counseling to husbands and wives about MKJP by offline (face to face, leaflets, brochures, etc.) and online (internet) during the Covid-19 period.